Pengaruh Implementasi Green Port terhadap Pencegahan Pencemaran Lingkungan Maritim di Pelabuhan Indonesia - Siringoringo, Cristian Jeferson; Nazarwin, Nazarwin (Jurnal Cakrawala Bahari, 2025)
Ports play a vital role as maritime transport hubs, logistics centers, and gateways for international trade. However, port operations also pose potential negative impacts on the marine environment, including water and air pollution as well as degradation of coastal ecosystems. To address these challenges, the Green Port concept emerges as a strategic solution that emphasizes sustainable port management through the adoption of environmentally friendly technologies, emission reduction, energy efficiency, and improved waste management systems. This study aims to analyze the influence of Green Port implementation on preventing marine environmental pollution in Indonesian ports. The research employs a descriptive qualitative approach through literature review, analysis of international and national regulations, and case studies of Green Port practices in several major Indonesian ports. The findings indicate that the implementation of Green Port significantly reduces pollution risks through the application of eco-friendly operational standards, development of waste treatment facilities, utilization of renewable energy, and digitalization of port systems to improve operational efficiency. Furthermore, adopting Green Port practices enhances the global competitiveness of Indonesian ports by aligning with international standards such as those set by the International Maritime Organization (IMO) and the Environmental Management System ISO 14001. The study concludes that the success of Green Port implementation relies not only on technological innovation but also on the commitment of government, port operators, and the awareness of all maritime stakeholders. Therefore, Green Port serves as an essential instrument in protecting environmental sustainability while supporting the growth of Indonesia’s maritime economy.